What the 1987 stock market crash foretold. - Waters, Mary-Alice, 1942-; Trotsky, Leon, 1879-1940.; Barnes, Jack. (New York : Pathfinder Press, 1994)
'This issue of New international looks at the consequences over the last seven years of the decelerating growth, heightened volatility, and increased instability that more and more form the pattern of international capitalism, a pattern signaled by the near-meltdown in October 1987 of stock markets from New York and London to Tokyo and Hong Kong.'
Defending Cuba, defending Cuba's socialist revolution / Mary-Alice Waters -- What the 1987 stock market crash foretold : resolution adopted by 1988 Socialist Workers party convention -- The curve of capitalist development / Leon Trotsky -- Imperialism's march toward fascism and war/ Jack Barnes.
Editor: Mary-Alice Waters, managing editor, Steve Clark.
At head of title: New international, a magazine of Marxist politics and theory.
Includes bibliographical references.
Koleksi sumbangan Tun (Dr.) Ahmad Sarji Abdul Hamid.
Keywords: Socialism; Communism; Imperialism